One-step DME synthesis from CO2/H2: Promoter effects, methanol synthesis reversibility, oxygen vacancies and catalyst deactivation - Priscila C. Zonetti; Eugenio F. de Souza; Guilherme G. Gonzalez; Luciano H. Chagas; Igor P.S. Pereira; Bruno H. Arpini; Frederico W. Tavares; Trong D. Pham; Michael P. Lanci; Alexandre B. Gaspar; Lucia G. Appel (Fuel, 2027)

What determines trophic niche breadth? A global analysis of freshwater fishes using isospaces - Friedrich Wolfgang Keppeler; Tommaso Giarrizzo; Carmen G. Montaña; Alphonse Adite; Şenol Akın; Ronaldo Angelini; Caroline C. Arantes; Evanilde Benedito; Thethela Bokhutlo; Rana El-Sabaawi; Alexandre Garcia; Ivan Gonzalez-Bergonzoni; et al. (Reviews in Fish Biology and Fisheries, 2026)

Phenotypic variability of hydraulic residual conductance and its temperature sensitivity in Abies alba Mill - Stéphane Herbette; Andanson Stéphane; Gonzalez Alexandre; J. Blackman Chris; Cartailler Julien; Martin Ludovic; Cochard Hervé (Trees, 2026)

Fights in a tight space: wax scale Ceroplastes deodorensis Hempel (Hemiptera: Coccidae: Ceroplastinae) and associated parasitoids (Hymenoptera: Chalcidoidea) on a new host plant (Arecaceae) - Nyeppson de Sousa Soares; Anne Caroline Santos Küll; Alexandre Santos Araújo; Gabriel Silva Dias; Ana Lúcia Benfatti Gonzalez Peronti; Leonardo Souza Duarte; Bianca Mendes de Almeida; Yanka Silva de Sousa; Valmir Antonio Costa; Roberto Antonio Zucchi; Marcoandre Savaris (International Journal of Tropical Insect Science, 2026)
The hosts of Ceroplastes deodorensis Hempel (Hemiptera: Coccidae) belong to the families Annonaceae and Moraceae, which are exclusively recorded in Brazil. In this report, we document for the first time the occurrence and impact of C. deodorensis on adult plants of the dwarf date palm, Phoenix roebelenii O’Brien (Arecaceae), in Brazil. The wax scale was collected and examined on P. roebelenii at the “Luiz de Queiroz” campus in Piracicaba, São Paulo, Brazil, between April 2024 and March 2025. The population of C. deodorensis peaked from April to October 2024, causing damage solely to the leaves (leaflets) of the dwarf date palm, which manifested as yellowing and drying. The scale insect was found to be parasitized by four species of Chalcidoidea from four families: Aprostocetus sp. (Eulophidae), Brasema sp. (Eupelmidae), Metaphycus floridensis Santos & Tavares (Encyrtidae) (new record), and Scutellista caerulea (Fonscolombe) (Eunotidae) (new record). Notably, M. floridensis and S. caerulea comprised over 90% of the total parasitoids collected. This study serves to compile and update information regarding the hosts and parasitoids of C. deodorensis.

From waste to value: Exploring the social representations of composting - Alexandre Lapeyre; Nawel Ayadi; Christine Gonzalez (Journal of Cleaner Production, 2025)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

Sensor detection of shelf life: a multi-technique food analytical platform for mushroom analysis - Patricia Yukari Saiki; Fernando Cesar Rufino; Cassio Roberto de Almeida; Geovana Manzan Sales; Arthur Noin de Oliveira; Dunieskys Roberto Gonzalez Larrude; Ricardo Cotrin Teixeira; José Alexandre Diniz; Rodrigo Ramos Catharino (Food Research International, 2025)

Biomonitoring of elements airborne pollution in European Mediterranean region by two Tillandsia species - Alexandre Gonzalez; Zohra Benfodda; David Bénimélis; Damien Bourgeois; Jean-Xavier Fontaine; Roland Molinié; Patrick Meffre (Atmospheric Pollution Research, 2025)

Determination of the maximum bioaccumulation capacity of various metals in leaves of two Tillandsia species - Alexandre Gonzalez; Zohra Benfodda; David Bénimélis; Damien Bourgeois; Damien Herfurth; Jean-Xavier Fontaine; Roland Molinié; Patrick Meffre (Environmental Science and Pollution Research, 2024)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

New records of the occurrence of biting midges (Diptera: Ceratopogonidae) species in rural area of Santa Maria, Rio Grande do Sul, in the South of Brazil - Julia Somavilla Lignon; Emanuelle de Souza Farias; Felipe Arley Costa Pessoa; Eduarda Maria Trentin Santi; Lucas Alexandre Farias de Souza; Gilneia da Rosa; Diego Moscarelli Pinto; Luciana Pötter; Silvia Gonzalez Monteiro (International Journal of Tropical Insect Science, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Combination of acute hypertensive striatocapsular hemorrhage and mirror previous asymptomatic slit-like hemorrhage in a young patient: a new radiological clue for cerebral small vessel disease? - Jonathan Leempoel; Amina Sellimi; Natalia Gonzalez Rodriguez de Azero; Alexandre Persu; Thierry Duprez (Acta Neurologica Belgica, 2021)

Genes and SNPs in the pathway of immune response and caries risk: a systematic review and meta-analysis - Luiz Alexandre Chisini; Mariana Gonzalez Cademartori; Marucs Cristian Muniz Conde; Francine Dos Santos Costa; Luciana Tovo-Rodrigues; Rodrigo Varella de Carvalho; Flávio Fernando Demarco; Marcos Britto Correa (Biofouling, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Chemometric and high-resolution mass spectrometry tools for the characterization and comparison of raw and treated wastewater samples of a pilot plant on the SIPIBEL site - Agneta Kiss; Alexandre Bergé; Bruno Domenjoud; Adriana Gonzalez-Ospina; Emmanuelle Vulliet (Environmental Science and Pollution Research, 2018)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Knowledge Recovery for Continental-Scale Mineral Exploration by Neural Networks - Laurent Bougrain; Maria Gonzalez; Vincent Bouchot; Daniel Cassard; Andor L. W. Lips; Frédéric Alexandre; Gilbert Stein (Natural Resources Research, 2003)